Compositionality and Concepts in Linguistics and Psychology - Hampton, James A.; Winter, Yoad; Hampton, James A.; Winter, Yoad; Hampton, James A.; Winter, Yoad (Cham Springer Nature, 2017)
cognitive science; semantics; language
English
Keywords: Language; cognitive science; semantics; language